Analisa Peran Ganda Pekerja Wanita Pada Pabrik Udang Bumi Menara Internusa (BMI) Dampit, Malang - Niko Ardiansah; Bahrul Ulum (CV Edujavare Publishing, 2025)
The term gender is a cultural product that has developed in society. Some communities adhere to a patriarchal culture that considers men superior to women, this leads to restrictions on women's rights. On the one hand, women around Dampit work outside the home, but their domestic duties must still be fulfilled, so they bear a double burden. This is certainly contrary to the term gender that is currently developing. The purpose of this study is to develop and understand the empirical facts of women, predominantly housewives, who work at the Bumi Menara Internusa (BMI) Shrimp Factory, who have roles in the household with issues regarding gender equity. The method used in this study is qualitative with a case study research type, while the technique in collecting data is by conducting in-depth and semi-structured interviews with participants as part of strengthening the research. In summary, the findings of this study are: the lives of workers at the Bumi Menara Internusa (BMI) Shrimp Factory in Dampit are in line with the concept of gender equity, moderate Islamic feminism and Zaitunah Subhan. Several industrial sectors require the role of women who are considered superior to men, and finally the women who work at the Bumi Menara Internusa (BMI) Shrimp Factory do not contradict the opinions of classical Ulama' regarding gender